(untitled) (Nueva Epoca, 2020)
The new civil and commercial code of the nation has strongly moved toward to prevention, resulting this prevention principle fully applicable to the contract field. In this way, the prevention of damage norms was introduced in the Code in the general regulation of liability (Articles 1710 and followings) and also in the specific contractual norms (Articles 1031 and 1032). This normative text aims to prevent damage and contractual conflicts as well, giving valuable tools to be used by parties and judges, solving contractual conflicts when required. Although the prudence that has to be apply for the users of these preventive measures that the code sets available, having in mind the risk of violating the private autonomy expressed in the contractual instrument, the interpretation should not be so restrictive to the point of depriving parties of the possibility to avoid damages or at least not deepening them, and above all, to the possibility of keeping the contract alive. We believe that, until now, the richness of the preventive principle introduced by the new code has not been fully exploited in the contractual field yet.